Susceptibility of Exotic Pines to Cronartium himalayense - Bakshi, B. K.; Singh, Sujan (Indian Forester, 1972)
Peridermium himalayense, the aecial stage of Cronartium himalayense on Indian chir pine, is recorded on Canary pine (Pinus canariensis), an exotic raised under 1965 trial planlation at Ranikhet, Western Himalayas. Where the chir pine and the rust both occur. The rust on Canary pine is highly destructive causing death of affected branches and the plant. P. patula, P. michoacana, P. pseudostrobus var. tenuifolia, P. pinea, P. montezumae, P. pseudostrobus, P. taeda, P. ayacahuite, P. ponderosa, P. radiata, P. sylvestris, P. pinaster, P. nigra, P. banksiana, P. kesiya, P. caribaea, P. elliottii and P. echinata raised in the localitly are so far free from attack due to the rust. Canary pine is planled extensively or on trial basis in many countries where Swertia may occur. The rust is likely to cause economic damage if inadvertently introduced in those countries.